ANALISIS STRATEGI PEMBERDAYAAN UMKM DALAM MENGHADAPI PERDAGANGAN BEBAS KAWASAN ASEAN (STUDI KASUS KAMPUNG KERAWANG GAYO) - Dian April Yani; Susi Apriliani; Satria Abdillah Hilman; Purnama Ramadani Silalahi (Universitas Maritim AMNI Semarang, 2023)
This research was carried out to find out how the strategy for empowering MSMEs in Kerawang Gayo village, Bebesen district in dealing with free trade in the ASEAN region. By using qualitative methods and based on emerging research strategy patterns. To understand and provide an explanation of the pattern of MSME development methods. For Indonesian MSMEs MEA is a big challenge as well as a market opportunity as well. Indonesian MSMEs, which so far are mostly inward looking, will likely experience quite tough challenges. The strategy he adopted in developing Kerawang Gayo SMEs was by modifying products that were more up-to-date following market trends but did not eliminate existing cultural values. And with the existence of social capital originating from Bank Aceh, it plays a role in the pattern of MSME development strategie.